TRABALHO RURAL: EXPOSIÇÃO A AGROTÓXICOS E A RADIAÇÃO UV - VIEIRA, CAROLINA P.; LIMA, FERNANDA O.; SANTOS, GREICE F. F. D.; BELLINASO, MARIA D. L.; GOETTENS, PAULINE B. (Salão do Conhecimento, 2013)
Resumo